Enhancing NMR quantum computation by optimizing spectroscopic parameters of potential qubit molecules - Lino, Jéssica Boreli dos Reis (2021)
Quantum computing is the field of science that uses quantum-mechanical phenomena, such as superposition and entanglement, to perform operations on data. The fundamental information unit used in quantum computing is the quantum bit or qubit. It is well known that quantum computers could theoretically be able to solve problems much more quickly than any classical computers. Currently, liquid state nuclear resonance magnetic (NMR) enriches quantum information processing (QIP) by inspiring new ideas for theoretical and experimental investigation, leading to technology for demonstrating quantum computing in small physical systems. Notwithstanding, molecules that enable many qubits NMR QIP implementations should meet some conditions regarding their spectroscopic properties. First, exceptionally large through-space (TS) P-P SSCCs observed in 1,8-diphosphanaphthalenes (PPN) and in naphtho[1,8-cd]-1,2-dithiole phenylphosphines (NTP) were proposed and investigated to provide more accurate control within large-scale NMR QIP. Spectroscopic properties of PPN and NTP derivatives, as chemical shifts and through-space spin-spin couplings were explored by theoretical strategies. From our results, the derivatives PPNo-F, PPNo-ethyl and PPNo-NH2 were the best candidates for quantum information processing via NMR, where the large TS J could circumvent the need of long-time quantum gate implementations. Which could, in principle, overcome natural limitations related to the development of large-scale NMR QIP. In the second paper, we report a computational design strategy for prescreening recently synthesized complexes of cadmium, mercury, tellurium, selenium, and phosphorus (called MRE complexes) as suitable qubit molecules for NMR QIP. Chemical shifts and spin−spin coupling constants in five MRE complexes were examined using the spin−orbit zeroth order regular approximation (ZORA) at the density functional theory level and the four-component relativistic Dirac-Kohn-Sham approach. Assembled together with the most common qubits used in NMR quantum computation experiments, spin-1/2 nuclei, such as 113Cd, 199Hg, 125Te, and 77Se, could leverage the prospective scalable quantum computer architectures, enabling many and heteronuclear qubits for NMR QIP implementations.